Adaptive resilience: Functioning of schools in the Wielkopolska region (Poland) during the COVID-19 pandemic - Tobolska, Anna; Bogacka, Emilia (Quaestiones Geographicae, 2025)
The main aim of the article is to determine the degree of adaptive resilience of the school education system to the crisis of the COVID-19 pandemic, both on the scale of a selected region, the Wielkopolska region in Poland, and a subregional scale, by poviats (counties). The school education system is one of the region’s social system spheres. The resilience study uses the results of a survey conducted among students, the most important stakeholders of this system. The selection of indicators to measure resilience was based on assessing adaptive actions that determine effective participation in online lessons. The results show a high level of students’ adaptation to the implementation of online classes on a regional scale and quite significant variation on a subregional scale. The article also formulates the assumptions of the adaptive resilience concept of the school education system in relation to the regional resilience concepts established in the literature. The presented concept of analysing the adaptive resilience of the education system assumes ex-post research, which is related to empirical research conducted after the outbreak of the pandemic and after schools had taken adaptive measures.